1991
DOI: 10.1055/s-2007-1024689
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and Cardiorespiratory Responses to the Performance of Wing Chun and T'ai Chi Chuan Exercise

Abstract: The primary purpose of this study was to examine the metabolic and cardiorespiratory responses to the continuous performance of Wing Chun and T'ai Chi Chuan exercise. No significant differences in VO2max or HRmax obtained during treadmill exercise were found between the practitioners of the two styles. Average values for oxygen uptake (VO2) were 23.3 +/- 7.5 ml.kg-1.min-1 (6.6 METS) and 16.0 +/- 3.9 ml.kg-1.min-1 (4.6 METS) for Wing Chun and T'ai Chi Chuan exercise, respectively. Mean heart rates obtained duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 2 publications
2
22
0
Order By: Relevance
“…This cardiovascular and metabolic high response observed in participants indicates that the work intensity achieved on the performed session was vigorous [23], and the increase of HR and La -post-exercise values regarding baseline values was significant (p<0.000). These findings are consistent with previous studies evaluating HR [14,24,25] and La -responses [14,[26][27][28]] during combats or training sessions of other combat sports.…”
Section: Discussionsupporting
confidence: 83%
“…This cardiovascular and metabolic high response observed in participants indicates that the work intensity achieved on the performed session was vigorous [23], and the increase of HR and La -post-exercise values regarding baseline values was significant (p<0.000). These findings are consistent with previous studies evaluating HR [14,24,25] and La -responses [14,[26][27][28]] during combats or training sessions of other combat sports.…”
Section: Discussionsupporting
confidence: 83%
“…Till now, there have been a number of studies concerning the physiological effects of TJQ on cardio-respiratory function (Schneider and Leung 1991;Brown et al, 1989;Hong et al, 2000), physical fitness (Hong et al, 2000;Lan et al, 1998), body composition (Lan et al, 1996) and immunity improvement (Sun et al, 1989) as well as the rehabilitation of cardio-respiratory function (Channer et al, 1996;Lan et al, 1999), arthritis (Farrell, 1999) and high blood pressure (Deborah, 1999) etc. In addition, Jin (1989Jin ( , 1992 reported that practice of TJQ was helpful to lessen tension, depression, anger, fatigue, confusion and state-anxiety, and made the practitioners feel more vigorous and lessened total mood disturbance.…”
Section: Introductionmentioning
confidence: 99%
“…[56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75] Of these, 13 eval- uated yoga, 20 tai chi, 9 qi gong, and 1 tai chi and qi gong combined. Yoga, tai chi, and qi gong are discussed together in this review.…”
Section: Resultsmentioning
confidence: 99%
“…48 Twenty-seven studied healthy people: older adults, 34,35,50,55,57,58,[60][61][62][63][64][65][73][74][75][76][77] healthy adults, 59 healthy males, 66,69 soldiers, 44 students, 46,53,71 children, 37 "residents," 59 and practitioners of tai chi/yoga. 56,67,68 The remaining 6 studies were on non-respiratory disorders (lower-limb disabilities, 70 breast cancer patients, 54 heart disease, 49 impaired vision, 36 Parkinson's disease, 40 and hypertension 39 ) but also measured respiratory outcomes. The majority of the studies involved adults; only 3 included children.…”
Section: Samplesmentioning
confidence: 99%
See 1 more Smart Citation